Mineralization and nitrification: Archaea dominate ammonia-oxidising communities in grassland soils. (April 2020) - Clark, Dave R.; McKew, Boyd A.; Dong, Liang F.; Leung, Garwai; Dumbrell, Alex J.; Stott, Andrew; Grant, Helen; Nedwell, David B.; Trimmer, Mark; Whitby, Corinne
Abstract: In grasslands, N mineralization and nitrification are important processes and are controlled by several factors, including the in situ microbial community composition. Nitrification involves ammonia oxidising archaea (AOA) and bacteria (AOB) and although AOA and AOB co-exist in soils, they respond differently to environmental characteristics and there is evidence of AOA/AOB niche differentiation. Here, we investigated temporal variation in N mineralization and nitrification rates, together with bacterial, archaeal and ammonia-oxidiser communities in grassland soils, on different geologies: clay, Greensand and Chalk. Across geologies, N mineralization and nitrification rates were slower in the autumn than the rest of the year. Turnover times for soil ammonium pools were <24 h, whilst several days for nitrate. In clay soils, bacterial, archaeal, AOA, and AOB communities were clearly distinct from those in Chalk and Greensand soils. Spatially and temporally, AOA were more abundant than AOB. Notably, Nitrososphaera were predominant, comprising 37.4% of archaeal communities, with the vast majority of AOA found in Chalk and Greensand soils. AOA abundance positively correlated with nitrate concentration, whereas AOB abundance correlated with ammonium and nitrite concentrations, suggesting that these N compounds may be potential drivers for AOA/AOB niche differentiation in these grassland soils. Highlights: Turnover times for soil ammonium were <24 h, whilst several days for nitrate. AOA and AOB communities in clay were clearly distinct from those in chalk and greensand soils. Generally, ammonia oxidising archaea were more abundant than ammonia oxidising bacteria. AOA abundance positively correlated with nitrate, whereas AOB abundance correlated with ammonium and nitrite concentrations. This study showed additional evidence for niche differentiation among ammonia-oxidisers in grasslands.